The Effect of Acupuncture Therapy on Stomach Pain with Stomach Qi Stagnation Syndrome - Chandra, Lindawati; Ferdinand, Ferdinand; Priskila, Onny (Rifa'Institute, 2023)
Introduction: Gastric disease, or gastric pain, is discomfort in the pit of the stomach, including nausea, vomiting, feeling full in the stomach, bloating, and belching. The main causes of gastric pain are irregular eating patterns, not being able to manage stress, consumption of alcohol and cigarettes, ulcers in the stomach, and side effects of anti-inflammatory drugs. Gastric pain treatment can be done in conventional and traditional ways. Traditional medicine by means of acupuncture is a treatment technique that involves inserting special needles into certain points. Objective: This study aims to analyze the effect of acupuncture therapy on Zhong Wan (CV 12), Zu San Li (ST 36), Qimen (LR 14), Taichong (LR 3), Weishu (BL 21), and Neiguan (PC 6) points of patients with gastric pain at the Mustika Surabaya Foundation. Method: This research method is qualitative with a case study approach. This research was conducted between October and December 2022 with 10 therapies. The data was collected through interviews and direct measurements of the respondents. Result and Discussion: The results of the study showed that there was a change in respondent’s statements that they became more comfortable and reduced pain after carrying out acupuncture therapy. Conclusion: Treatment using the acupuncture method can effectively treat gastric pain